Surface passivation for silicon solar cells using stable extrinsic field effect passivation - Collett, K (2018)
One of the largest challenges for high efficiency solar panels is the recombination of photo-generated carriers at the silicon surface. This recombination can be reduced by both chemical passivation and Field Effect Passivation (FEP). Conventionally, this is achieved by the SiNx antireflection coating. However, this is sub-optimal and insufficient for high efficiency devices. This thesis focuses on introducing FEP, independent of the antireflection coating, to allow superior surface passivation to be achieved. The alneal, a process of annealing aluminium covered oxide layers, is known to provide excellent surface passivation, was investigated. This already superior surface passivation method could be improved with the addition of sodium and potassium ions at the SiO2-Si interface, termed ionic-FEP. This produced record-breaking surface passivation with a surface recombination velocity (SRV) of 0.15 cm/s and a surface saturation current denisty (J0s) of 0.1 fA/cm2 on 1 Wcm n-type float zone (FZ) Si. A mechanism is described that explains ion introduction during this process. It offers an explanation as to why the passivation is achieved so rapidly, requiring an anneal of under 15 seconds at 450 °C, and places emphasis on the importance of an electric field between the oxide surface and silicon substrate during ion introduction. The requirement for an electric field for fast ionic migration is utilised in developing an industrially scalable technique for introducing ionic-FEP. Ionic precursors are deposited onto the SiO2 surface by spin or spray coating. The migration process comprises two stages: corona charge deposition to provide the electric field for migration and an anneal at 450 °C. Using potassium, there was found to be a linear, almost one-to-one, relationship between corona surface charge and resulting interface charge after annealing. The anneal time required for potassium ion introduction at 450 °C was found to be under two seconds. This process achieved a SRV of 3.3 cm/s, equivalent to a J0s of 8.4 fA/cm2 on 1 Wcm n-type FZ Si. The addition of hydrogen to an ionically-passivated SiO2-Si interface was tested. It was found that hydrogen was able to increase the effective lifetime of 200 μm thick 1 Wcm n-type FZ Si from 1800 μs to 3000 μs. As the interface charge concentration for this experiment was not optimal, it is likely that with the right charge concentration this process could provide surface passivation of a similar quality as the ion-enhanced alneal. Alternative ionic species for FEP were trialled. Larger ions were tested following the hypothesis that they may be more strongly bound to the SiO2-Si interface. Rubidium was successfully introduced, although the process required minutes rather than seconds. An effective lifetime of 1800 μs was achieved, which is comparable to that realised using potassium at the same concentration. Calcium showed promise, but the successful introduction of the species could not be concluded. Magnesium and Strontium seem unable to be introduced into the SiO2-Si system as charged species.